Adverse social experiences in adolescent rats result in persistent sex-dependent effects on alcohol-seeking behavior - Graf, Akseli; Vengeliene, Valentina; Skorodumov, Ivan; Meinhardt, Marcus; Hansson, Anita C.; Spanagel, Rainer (Alcoholism, 2021)
Background Accumulating clinical evidence suggests that women with prior exposure to adverse childhood experiences are more susceptible to heavy drinking and other health-related behaviors. Yet, preclinical studies investigating sex-dependent effects of adolescent adverse social experiences (ASEs) on later alcohol-seeking behavior are lacking. This is mainly due to the unavailability of valid animal models and a shortage of studies that compare effects in males and females. Therefore, we sought to investigate the sex-dependent effects of ASE on adult alcohol-seeking behavior, locomotion, and reward sensitivity in male and female rats. Methods We recently developed a rat model for childhood/adolescent peer rejection that allows us to study the long-term consequences of ASEs. Adolescent Wistar rats were reared from postnatal day (pd) 21 to pd 50 either within a group of Fischer 344 rats (ASE) or within a group of Wistar rats (control). Wistar rats housed with Fischer 344 rats do not reciprocate social play in adolescence. This reduced play across adolescence mimics peer rejection and results in chronic dysregulation of social and pain-related behaviors. We tested adult male and female rats in the reinstatement paradigm for cue-induced alcohol-seeking behavior, circadian locomotor activity, and sucrose consumption long after the termination of the peer rejection condition. Results Peer rejection induced persistent sex-dependent changes in alcohol cue-induced reinstatement. Females showed an increased reinstatement effect while peer-rejected males demonstrated a decrease. Sex differences were observed in locomotor activity or reward sensitivity to sucrose. Conclusions Peer rejection has long-lasting sex-dependent consequences on alcohol-seeking behavior without affecting locomotion or sweet reward sensitivity. Our results suggest that peer-rejected female rats represent a vulnerable population in which to study relapse-like behaviors that are similar to clinical findings, while males seem to buffer the peer rejection effect and demonstrate resilience to later life alcohol-seeking behaviors, as measured by the reinstatement effect. Finally, we provide a novel approach to investigate the molecular and neurobiological underpinnings of ASEs on alcohol and other drug-seeking behaviors.
17 July 2021
Gesehen am 30.05.2022